Chronic pain: its impact on the quality of life and gender - Pandelani, Funeka Faith; Nyalunga, Suzan Louisa Nnanile; Mogotsi, Miriam Morongwa; Mkhatshwa, Vangile Bridget (Frontiers in Pain Research, 2023)
Background Chronic pain poses a considerable challenge to individuals' well-being, leading to decreased quality of life, limitations in daily functioning, and a higher reliance on healthcare services, resulting in significant economic burdens. In South Africa, chronic pain ranks among the prevalent chronic health conditions, although the exact prevalence might differ across different regions. To address this issue effectively, it is crucial to gain a comprehensive understanding of the problem by utilising the most up-to-date and relevant data available. Aim The aim of this study was to assess the impact of chronic pain on the quality of life and gender of the patients attending a primary healthcare centre. Methods We conducted a cross-sectional quantitative study among chronic care patients at Soshanguve Community Health Centre (CHC). The study utilized a validated Wisconsin Brief Pain Questionnaire to collect data. A total of 331 patients actively participated in the study. Results The prevalence of chronic pain was 21.5% [95% CI: 17.0–25.9]. Females were affected more frequently than male patients, chronic pain was 11.1% greater in females than in male. Furthermore, chronic pain mildly impacted the general activity of patients 33.8% [95% CI: 23.9–45.4], mood 42.3% [ 95% CI: 31.4–53.8], walking ability 29.6% [95% CI: 20.2–41.0], relationships 47.9% [95% CI: 36.7–59.3), sleep 31.0% [95% CI: 21.4–42.5], enjoyment of life 39.4% [95% CI: 28.9–51.1] and normal working ability 25.3% [ 95% CI: 16.7–36.6]. Conclusions The exact Fisher test conducted to assess the association between the experienced chronic pain and its impact on the quality of life yielded a significant result, with a p-value of 0.0071 (p < 0.05). This indicates that a considerable number of patients are currently enduring chronic pain that has a noticeable effect on their overall quality of life. These findings offer invaluable insights that are essential for enhancing resource allocation at the primary care level and facilitating a more comprehensive evaluation of pain management in our communities.